2021
DOI: 10.32859/era.21.27.1-18
|View full text |Cite
|
Sign up to set email alerts
|

Ethnobotanical survey on plants used by traditional healers to fight against COVID-19 in Fez city, Northern Morocco

Abstract: Background: Coronavirus disease 2019 (COVID-19) has now been spread around the world in the form of a highly contagious pandemic. The lack of effective vaccines against this lethal viral infection is pushing researchers to identify potential sources from natural products that can help fight the pandemic. In Morocco, medicinal and aromatic plants (MAPs) have long been used to combat infectious diseases. According to our knowledge, this is the first ethnobotanical survey in Fez city, aimed to quantify the ethnob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 34 publications
9
9
0
Order By: Relevance
“…Generally, the majority (55.4%) of the people with indigenous knowledge in this study were older than age 51. This result is similar to previous reports on the ethnobotanical survey of indigenous medicinal plants in Nigeria [ 24 ] and Northern Morocco [ 36 ]. The predominance of elderly participants with indigenous knowledge in the present study agrees with previous reports that older people (above age 50) are usually more knowledgeable about the practice of herbal medicine [ 24 ].…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Generally, the majority (55.4%) of the people with indigenous knowledge in this study were older than age 51. This result is similar to previous reports on the ethnobotanical survey of indigenous medicinal plants in Nigeria [ 24 ] and Northern Morocco [ 36 ]. The predominance of elderly participants with indigenous knowledge in the present study agrees with previous reports that older people (above age 50) are usually more knowledgeable about the practice of herbal medicine [ 24 ].…”
Section: Resultssupporting
confidence: 92%
“…Regarding the level of education, individuals with a tertiary education level constituted the minority (19.64%) of the participants. This result may be attributed to the fact that the practice of traditional medicine or herbalism does not require a degree but is acquired by experience and learning from older generations [ 36 ]. Our result is in line with an ethnobotanical survey of local flora used for medicinal purposes conducted in Lagos, Nigeria, which reported that 79% of the participants with indigenous knowledge had only a primary education [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…In Morocco, the most commonly used medicinal plant against COVID-19 was Eucalyptus globulus Labill., which was reported in 3 different studies [ 25 , 32 , 44 ]. Eucalyptus globulus Labill., its essential oils, and active compounds have antiviral effects and anti-infective properties [ 16 , 30 ].…”
Section: Main Textmentioning
confidence: 66%
“…& L.M.Perry , Thymus vulgaris L., Eucalyptus globulus Labill . , and Artemisia vulgaris L Benkhaira et al [ 25 ] North-Western Morocco 20 Eucalyptus globulus Labill . , Azadirachta indica A.Juss.…”
Section: Main Textmentioning
confidence: 99%
“…It is well seen that the amount and nature of these volatile compounds vary according to the harvest seasons and environmental factors, including geographical origin, phenological stage, and genotype. This variation also depends on the experimental conditions, including the drying process, storage, oil extraction method, and the plant's part used (55)(56)(57)(58). According to the available studies, we notice that the RM plant is more studied in Algeria, it is therefore recommended to examine the RM plants of other regions and countries, and it is quite remarkable that besides leaves, flowers, and stems, other plant parts need further studies to reveal new bioactive molecules.…”
Section: Volatile Compoundsmentioning
confidence: 99%